INSURANCE REGULATION IN THE RUSSIAN FEDERATION AND EURASEC MEMBER COUNTRIES - I. V. Putilin (Финансы: теория и практика)
The paper discusses the ways of rapprochement of insurance legislations of EurAsEC Member States. It evaluates the role of unification and harmonization in this process. When considering the unification, the author pays attention to legal mechanisms of its two stер implementation. Also, the author considers the role and importance of harmonization and unification of insurance sources in the EurAsEC member states in terms of their rapprochement. Based on the analysis of the unification and harmonization category, it is suggested to adopt the EurAsEC Treaty on the insurance and the Model Code with the aim to use their provisions in national legal systems of member states. The current law tries to meet the challenges of the day in the field of international insurance business; it looks for ways and means to optimize regulation of legal and economic activities and at the same time to respect national legislations. The whole process is proceeding towards unification of regulatory documents with further uniform regulation within the economic union.